2018
DOI: 10.1080/13557858.2018.1469735
|View full text |Cite
|
Sign up to set email alerts
|

The color of death: race, observed skin tone, and all-cause mortality in the United States

Abstract: Objective This paper examines how mortality covaries with observed skin tone among blacks and in relation to whites. Additionally, the study analyzes the extent to which social factors such as socioeconomic status affect this relationship. Design This study uses data from the 1982 General Social Survey (N = 1,689) data linked to the National Death Index until 2008. We use this data to examine the links between race, observed skin tone among blacks, and all-cause mortality. Piecewise exponential hazard modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…For instance, we note skin tone was determined to be an important predictor of all-cause mortality in the random forest algorithms. This is interestingly supported by a US study on the spectrum of skin tone and mortality [27]. Both residential air pollution and exposure to hazardous materials, consistent with findings from China [28] and Europe [29], are important variables in the deep learning model.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, we note skin tone was determined to be an important predictor of all-cause mortality in the random forest algorithms. This is interestingly supported by a US study on the spectrum of skin tone and mortality [27]. Both residential air pollution and exposure to hazardous materials, consistent with findings from China [28] and Europe [29], are important variables in the deep learning model.…”
Section: Discussionsupporting
confidence: 68%
“…There are also associations between skin tone and physical-health outcomes such as hypertension (Klag, Wheton, Coresh, Grim, & Kuller, 1991; Klonoff & Landrine, 2000; Sweet, McDade, Kiefe, & Liu, 2007; Tyroler & James, 1978) and mortality (Knap et al, 1995; Stewart, Cobb, & Keith, 2018). Klonoff and Landrine (2000) investigated darker complexioned individuals’ rates of hypertension and found that darker skinned African Americans are more likely to experience racist events and are more likely to develop hypertension.…”
Section: Skin-tone Traumamentioning
confidence: 99%
“…The GSS is a veritable goldmine for population health researchers because it contains variables not available in any other dataset. The GSS-NDI has been used in studies linking social characteristics such as exposure to individual-and institutional-level discrimination, sexual minority status, happiness, political ideology, emotion suppression, observed skin tone, and other statuses, attitudes, and behaviors with adult mortality risk (Chapman et al 2013;Lawrence et al 2015;Lee et al 2015;Morey et al 2018;Muennig et al 2013;Pabayo et al 2015;Stewart et al 2018). Researchers could not have established these associations with any other nationally-representative datasets.…”
Section: Survey-linked Mortality Filesmentioning
confidence: 99%